Early Literacy Assistance Regarding Fraud and its Resolution during the Covid Pandemic at Sagan Muhammadiyah Elementary School: Pendampingan Dini Literasi Mengenai Fraud dan Penyelesaiannya di Masa Pandemi Covid di SD Muhammadiyah Sagan - Fitriyanti, Fadia; Setyorini, Kusumaningdyah Retno (Universitas Lancang Kuning, 2024)
During the Covid pandemic, SD Muhammadiyah Sagan held an online school. There are several obstacles in learning activities faced by SD Muhammadiyah Sagan during this Covid pandemic. PJJ is known as distance learning (online) has various advantages in addition to disadvantages, including being prone to fraud or irregularities in the form of learning for 6th grade elementary school children, being required to study independently during the PJJ period, this does not cover the possibility of the occurrence of such fraud. including cheating during exams or during closed quizzes/questions, for example, students very easily commit dishonest acts, because online learning, especially using online applications, is not supervised by the teacher directly and is still vulnerable to fraudulent actions. The solution offered for this problem is the need to socialize fraud and its resolution and practice simulations through games, material presentations and pre-post test questions that will be given to 5th grade students of SD Muhammadiyah Sagan. The method offered in this community service program is to organize socialization and games. From the results of monitoring and evaluation of pre and post tests conducted before and after service activities, there is an increase in the assessment that students understand very well about fraud and settlement as many as 7 out of 18 became 25 and less score decreased by one from 3 to 2 after the post test. So that the overall understanding of the fifth grade elementary school students at Muhammadiyah Sagan Elementary School of fraud and its resolution has increased.